Integrating Blended Learning in Global Energy Education: Efficacy Evaluation & Insights from the 3D Energy Project Pilot - Yew W.K.; Ewe L.S.; Goh H.H.; Tuan D.-H.; Phan Q.D.; Dennis Wong M.L. (Association for Computing Machinery, 2025)
The rapid paradigm shifts in the global energy industry has emphasize a great need for a workforce that is well-equipped to combat its multifaceted challenges. Although blended learning models have become more common in numerous educational domains, their role in global energy education is not very well established. This paper focuses on evaluating blended learning within the context of the Decarbonisation, Decentralisation, and Digitalisation (3D) Energy Project to further our identification and understanding of a sustainable global energy education learning model. In this research, a novel learning programme involving a physical summit coupled with an online microcredential course, was introduced. This programme conducted a pilot study, which involved a group of postgraduate and final year undergraduate students from Malaysia, Vietnam, and China. Using quantitative and qualitative feedback, this paper sought to assess the summit's efficacy in fostering international collaborations and broadening participants' perspectives on energy challenges. Our principal findings indicate that participants greatly valued the opportunity for cross-cultural interactions, gained a deeper comprehension of energy-related topics, and found the course structure to be beneficial. Furthermore, the feedback revealed certain areas for improvement, such as additional language assistance and an extension to the physical summit for more in-depth interactions between countries. To summarise, the programme's blended learning approach highlighted it's potential for the future of global energy education. ? 2024 Owner/Author.